DAMPAK CALISTUNG TERHADAP PERKEMBANGAN EMOSI ANAK 5-6 TAHUN DI PAUD FADULLAH KID’S PEKANBARU - Putri Clawson; Ravida Roleza (Jurnal Ta'lim : Journal Ilmu Pendidikan dan Ilmu Keguruan, 2020)
This study aims to see and analyze the impact of calistung on the emotional development of children aged 5-6 years in Fadillah Kid's PAUD Pekanbaru City. This type of research is qualitative. This research is located in Fadillah Kid's PAUD, Pekanbaru City. The choice of this location is based on the consideration that the problems studied are in this location. Based on the results of interviews and observations (observations) researchers in the field about the "Impact of Calistung on Emotional Development of Children Aged 5-6 Years in PAUD Fadillah Kid, Pekanbaru City" is good. this seems that the teacher has not been able to provide interesting learning for children in developing children's emotions. The teacher teaches children by using educational toys, playing while learning, interesting media, and the child does not lose his world that is playing. And children express their emotions with reactions of joy, anger, sadness, fear, surprise, annoyance, and shame. And based on the writer's observation of children about the Impact of Calistung on the Development of Emotions Children can already recognize by playing and learning, children have started to develop their emotions well and children do not feel bored and bored in learning calistung.